Investigación de la incidencia de los recursos monetarios que el sistema financiero Ecuatoriano ha puesto a disposición de la iniciativa privada y pública para la generación de turismo en el Cantón Quito, para el período 2006-2011 - Flores Alvear, Sandra Gabriela (2012)
Methodological and practical guide to the process will be provided to follow in carrying out a research project in the tourism sector; same instrument that will serve as mentor to both teachers and students and enhance the prestige of the research area of the Faculty of Economics and Administrative Sciences Salesian University.